Application and prospect of Solution-focused brief therapy in psychiatry - Zhu, Zhenyu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the development of society, the incidence of mental illness is gradually increasing, and there are higher requirements for the quality of psychiatric diagnosis and treatment. At present, the lack of doctor-patient communication is in place is still the most important factor affecting the satisfaction of psychiatric diagnosis and treatment. An increasing number of studies focus on Solution-focused brief therapy in the diagnosis and treatment of mental illness to improve satisfaction and improve the doctor-patient relationship. Therefore, this paper screened and sorted out the relevant research literature on the Solution-focused brief therapy, and introduced the basic concepts and technologies of focus on Solution-focused brief therapy, so as to explore the practice and application prospects in psychiatry.